(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
A 30years of old hypothyroid lady , presented with foul smelling excessive whitish per vaginal discharge, associated with itching in vulva & pain in the lower abdomen following caesarean section 3 months back. Her uterus was palpably enlarged and firm. USG revealed bulky uterus with wall echo shadow sign. A CT scan of whole abdomen was done that revealed intrauterine textiloma. During laparotomy huge amount of pus came out through wound and a mob was found within uterine cavity. Textiloma is a rare problem of surgery arising from retained gauze during operation. Careful counting of surgical gauze before closure and identification by newer techniques is required to prevent this iatrogenic complication DOI: http://dx.doi.org/10.3329/bjog.v26i2.13791 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 100-102